Identification and characterization of Salmonella typhi isolates from Southwest Sumba District, East Nusa Tenggara based on 16S rRNA gene sequences - , Charis Amarantini ([Yogyakarta] : Sebelas Maret University, 2011)
Amarantini C. Sembiring L. Kushadiwijaya H. Asmara W (201I) Identification and characterization of Salmonella typhi isolatesfrom Southwest Sumba District. East Nusa Tenggara based on 16S rRNA gene sequences. Biodiversitas 12: 1-6. The incidence rate of typhoid fever in the Southwest Sumba District, East Nusa Tenggara was approximately about 725/100,000. In spite of such rate, there was not much known-yet about the molecular epidemiology of the disease. Thus, having accurate data and a strong discriminatory ability was crucial to scrutinize the molecular epidemiology of S. typhi with a molecular phylogenetic approach based on 16S rRNA gene sequences. Sixteen isolates representative of S. typhi from different geographical regions in Southwest Sumba District along with the reference strain S. typhi NCTC 786 had been identified and characterised based on 16S rRNA gene sequences using PCR amplification and sequencing. The 16S rRNA sequences data were aligned with the corresponding ayailable S. typhi sequences retrieved from the NCBI database by using CLUSTAL X software. Phylogenetic trees were generated with PHYLIP software package. Molecular phylogenetic analysis indicated that all the isolates belong to S. typhi species were suggested by their relativity with the type strain of S. typhi ATCC 19430T. It was also found that the isolates which belong to S. typhi species formed several different centers of diversity within the 16S rRNA gene tree. Each clade consisted of the strains from different geographical places in the District. Thus, to conclude the inquiry, there was evident inter-geographical spread of the strains and it tended to spread further into more remote areas in the District.